Hydrometallurgical removal of uranium and thorium from Ethiopian tantalite ore - Cheru, M.; del Rosario, A.; Yimam, A.; Tadesse, Bogale; Berhe, G. (Wroclaw University of Science and Technology, 2018)
This study focused on the leaching of uranium and thorium from a high grade Ethiopian tantalite ore using sulfuric acid. The effects of variables such as acid concentration, temperature and leaching time were studied. In general, the leaching efficiency of uranium increases with increasing temperature from 100 to 300 °C whereas the opposite trend was observed for thorium. The amount of uranium leached increased from 69.1% at contact time of 1 hr to 88.6% when the tantalite ore was leached for 3 hrs. On the other hand, for the experiments conditions considered in this study, the leaching behavior of uranium and thorium did not change significantly with varying sulphuric acid concentration from 70 to 90 wt%. Overall, the highest dissolution of uranium and thorium were achieved at 100 °C, 70 wt% H2SO4 concentration and 1 hr contact time.